Outil Présantés: verso un nuovo equilibrio tra osservazione e intervento diretto - Fano, Matteo; Magnani, Carlotta (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
This contribution retraces how the authors evolved their research approach on the homeless access to health-care system in the city of Marseille (France): from an applied anthropology project, whose aim was to build a knowledge base addressed to improve other professionals’ innovative actions; to a collaborative approach in which anthropologists can get directly involved in the action by creating and coordinating a network of actors. We also want to describe how this participative project sets up an IT tool to improve health-care orientations for homeless people, and consequently become a way to establish a collaborative network between social and health low-threshold services in the city. Through the analysis of this project evolution, we want to examine both practical and theoretical implications of our approach, and the particular shift in the role of the researcher, who get more implicated in the action and on its possible future developments.